2009
DOI: 10.1002/tea.20343
|View full text |Cite
|
Sign up to set email alerts
|

Teaching about ethics through socioscientific issues in physics and chemistry: Teacher candidates' beliefs

Abstract: The purpose of this qualitative study was to identify and explain the origins of physics and chemistry teacher candidates' beliefs about teaching about ethics through socioscientific issues (SSI). This study utilized a series of in-depth interviews, while the participants (n ¼ 12) were enrolled in a 9-month teacher education program at an urban university in Canada. Our data analysis revealed that beliefs about teaching physics and chemistry using SSI derive from a complex web of fundamental beliefs exemplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
2
18
1
1
Order By: Relevance
“…The instrumental way of operationalising socioscientific issues has been quite well documented in science education research -e.g. by Barrett and Nieswandt (2010) who found that some teachers' "purpose of including ethics is to get students interested long enough to teach them the facts and the theories of science or to get them to like science for its own sake" (p. 391).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrumental way of operationalising socioscientific issues has been quite well documented in science education research -e.g. by Barrett and Nieswandt (2010) who found that some teachers' "purpose of including ethics is to get students interested long enough to teach them the facts and the theories of science or to get them to like science for its own sake" (p. 391).…”
Section: Discussionmentioning
confidence: 99%
“…in the form of professional development or more systemic interventions), we believe that more knowledge is needed about teachers' beliefs vis-à-vis socioscientific issues in general -a vista explored by e.g. Barrett and Nieswandt (2010). In particular, we need to accumulate knowledge about how teachers from a variety of educational contexts interpret socioscientific issues and operationalise such issues in socioscientific teaching.…”
Section: Challenges To the Uptake Of Socioscientific Issuesmentioning
confidence: 99%
“…However, during participation in the OM program, they gradually developed their practices to incorporate social dimensions. To support this finding, Barrett and Nieswandt (2010) found that successful SSIs-based teaching depends on the teachers' awareness of social considerations associated with the issue, such as potential political, economic, and ethical challenges. In addition, they use media from the internet to link their lesson with social dimensions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, they are not committed to including SSI in their classroom. For existing studies, many factors may influence science teachers' practices, such as time limitation, unavailability of proper teaching materials, and/or lack of necessary knowledge for addressing SSI (Barrett and Nieswandt 2010;Bryce and Gray 2004). Moreover, it is likely that a lack of knowledge of ethics and its approaches among science teachers also hindered their SSI teaching (e.g., Kara 2012;Ludmark 2002;Slingsby 2008).…”
Section: Ssi-based Instructionmentioning
confidence: 99%